Atrio-Ventricular Septal Defect in Pregnant Women, How to Deal with it: A Case Study - Caroline D. &; Yogiarto M (ACI (Acta Cardiologia Indonesiana), 2017)
Atrio-Ventricular Septal Defect in Pregnant Women, How to Deal with it: A Case Study